1990
DOI: 10.1136/jmg.27.9.588
|View full text |Cite
|
Sign up to set email alerts
|

Partial monosomy for chromosome 22 in a patient with del(22)(pter----q13.1::q13.33----qter).

Abstract: An 18 month old girl with partial monosomy for the long arm of chromosome 22 is described. The karyotype was 46,XX,del(22)(pter-*ql3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 5 publications
1
41
1
Order By: Relevance
“…The phenotype of one 14 closely matches with that of the terminal 22q13 deletion syndrome with developmental delay, delay of expressive speech, hypotonia, overgrowth, ptosis, full cheeks, as well as several other minor dysmorphisms observed with the 22q13 deletion syndrome. As this case was never characterized molecularly, it is possible that this patient has a terminal rather than interstitial deletion of 22q13.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The phenotype of one 14 closely matches with that of the terminal 22q13 deletion syndrome with developmental delay, delay of expressive speech, hypotonia, overgrowth, ptosis, full cheeks, as well as several other minor dysmorphisms observed with the 22q13 deletion syndrome. As this case was never characterized molecularly, it is possible that this patient has a terminal rather than interstitial deletion of 22q13.…”
Section: Discussionmentioning
confidence: 54%
“…A cell line (EB33) from the patient described in Fujita et al 15 was used to compare the interstitial deletion in this patient to the interstitial deletions present in our patients (material was not available for the patient described in Romain et al 14 ). The FISH probes used by have not yet been mapped on the published genomic sequence available through NCBI.…”
Section: Molecular Analysis: Definition Of the Deletionmentioning
confidence: 99%
“…To our knowledge, however, deletion of 22q13 band has been reported in only 18 patients [Herman et al, 1988;Romain et al, 1990;Zwaigenbaum et al, 1990;Narahara et al, 1992;Phelan et al, 1992;Nesslinger et al, 1994;Dohney et al, 1997;Wong et al, 1997;Schröder et al, 1998]. All of them were a terminal deletion involving 22q13, but only one had interstitial deletion of this segment [Romain et al, 1990].…”
Section: Introductionmentioning
confidence: 93%
“…Intellectual impairment, hypotonia, normal to accelerated growth, absent to severely delayed speech, and minor dysmorphic features emerged as common characteristics of individuals with deletion of 22q13.3 [Watt et al, 1985;Kirshenbaum et al, 1988;Romain et al, 1990;Zwaigenbaum et al, 1990;Narahara et al, 1992]. Nesslinger et al [1994] first suggested that this was the recognizable phenotype of deletion 22q13.3, and they narrowed the critical region of overlap from a proximal breakpoint below D22S97 to a region distal to ARSA , a distance of less than 25.5 cM.…”
mentioning
confidence: 99%